Peranan Penyuluh Agama Islam dalam Memperbaiki Perilaku Narapidana di Lembaga Pemasyarakatan Kelas II A Metro Lampung (Jurnal Bimbingan dan Konseling Islam, 2020)
An Islamic religious instructor is someone who has knowledge of Islam, who is a guide, motivator and role model for people who listen to what he has to say. Therefore, the authors conducted a study on the role of Islamic extension agents in improving the behavior of prisoners to be better than before. The object of this research is all Muslim prisoners. Researchers use the method of observation or direct observation, interviews and documentation. Observations were made to find out about the condition of the prisoners and the location of the Class II A Metro Prison, to find out the activities carried out, the attitudes or behavior of the prisoners, the ways of implementing religious coaching activities by Islamic religious instructors. The interview method was carried out to obtain information related to the way the coaching activities were carried out, the time and place were carried out to the officers who regulated the course of these activities, namely the Community Health Center, as well as the prisoners themselves. The documentation method is used to obtain data on the prisoners, the composition of the organization, the schedule for the implementation of coaching activities. The author's data analysis used a qualitative descriptive approach, namely the data that had been obtained was written and described, accompanied by discussion and then drawing conclusions. The results showed that the role of Islamic religious instructors in improving the behavior of prisoners in the Class II A Metro Correctional Institution, in fact showed a positive attitude, namely the behavior that initially was less good than the prisoners became better after participating in religious activities delivered by the Islamic religious extension. This can be seen from the activeness of the inmates performing congregational prayers and carrying out sunnah prayers such as sunnah prayers and sunnah fasting, and being able to interact and behave well with fellow prisoners in the prison in the form of mutual tolerance and not easily emotional. The driving and inhibiting factors of the implementation of guidance from Islamic religious extension agents, among others, come from external and internal factors